2015
DOI: 10.1016/j.nbd.2015.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Differential recruitment of UBQLN2 to nuclear inclusions in the polyglutamine diseases HD and SCA3

Abstract: Accumulation of mutant polyglutamine proteins in intraneuronal inclusions is a hallmark of polyglutamine diseases. Impairment of protein clearance systems and sequestration of clearance-related proteins into inclusions occur in many protein folding diseases, including the polyglutamine diseases. The ubiquitin-binding and proteasome adaptor protein UBQLN2 participates in protein homeostasis and localizes to inclusions in various neurodegenerative diseases. Employing mouse models and human brain tissue of Huntin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…Htt-NTFs consist of a 17-residue N-terminal stretch (MATLEKLMKAFESLKSF) designated as N17, a polyQ tract of length n (Q n ), and a 38-residue C-terminal stretch (C38) that includes two polyproline (polyP) modules P 11 and P 10 connected by a 17-residue linker denoted as L17 (QLPQPPPQAQPLLPQPQ) (Figure 1a). In transgenic mouse models, Htt-NTFs produce robust degeneration of the relevant neurons (35).Although HD is characterized by Htt-NTF inclusions, the role of these inclusions as agents of neurotoxicity has been the topic of considerable debate (34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44). In a recent study, Ramzdan et al showed that both soluble species and insoluble deposits engender neurotoxicity, albeit through very different mechanisms (45).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Htt-NTFs consist of a 17-residue N-terminal stretch (MATLEKLMKAFESLKSF) designated as N17, a polyQ tract of length n (Q n ), and a 38-residue C-terminal stretch (C38) that includes two polyproline (polyP) modules P 11 and P 10 connected by a 17-residue linker denoted as L17 (QLPQPPPQAQPLLPQPQ) (Figure 1a). In transgenic mouse models, Htt-NTFs produce robust degeneration of the relevant neurons (35).Although HD is characterized by Htt-NTF inclusions, the role of these inclusions as agents of neurotoxicity has been the topic of considerable debate (34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44). In a recent study, Ramzdan et al showed that both soluble species and insoluble deposits engender neurotoxicity, albeit through very different mechanisms (45).…”
mentioning
confidence: 99%
“…Although HD is characterized by Htt-NTF inclusions, the role of these inclusions as agents of neurotoxicity has been the topic of considerable debate (34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44). In a recent study, Ramzdan et al showed that both soluble species and insoluble deposits engender neurotoxicity, albeit through very different mechanisms (45).…”
mentioning
confidence: 99%
“…Besides the disease‐related proteins, the protein inclusions also contain various other cellular partners, including components of the ubiquitin (Ub)‐proteasome system (UPS) (510), autophagy receptors (1113), molecular chaperones (1416), and transcription factors (1719). For different pathogenic proteins, some components colocalized within the inclusions are unique, whereas some are identical, such as Ub and Ub chains (6, 9, 2022), proteasome components (5, 7, 8, 10), sequestosome‐1/P62 (11), human RAD23 homolog B (hHR23B) (23, 24), ubiquilin (UBQLN)‐2 (25), valosin‐containing protein (VCP)/P97 (26, 27), and so on. Then, why the inclusions formed by different ND‐pathogenic proteins commonly contain Ub or Ub‐related proteins remains to be elucidated.…”
mentioning
confidence: 99%
“…Recently, accumulating evidence has demonstrated that sequestration of cellular interacting partners by protein aggregates or inclusions is a common source of cytotoxicity and neurodegeneration of NDs (16, 23, 2530). Based on recent research, it is likely that specific molecular interaction is the prerequisite for sequestration by protein aggregates (28, 31, 32).…”
mentioning
confidence: 99%
“…Mutations in Atx3 and P62, which disrupt their interactions with Ub, abolish their recruitments into the polyQ aggregates , implying that other normal Ub‐binding proteins are also sequestered in the same way. Interestingly, recent research showed that ubiquilin‐2, a proteasome adaptor with Ub‐binding ability, is selectively sequestered into the inclusions in HD, but not in spinocerebellar ataxia 3 (SCA3), due to its interaction with mutant Htt via the UBA domain , implying that the components of UPS may be differentially sequestered into inclusions in different types of NDs.…”
Section: Specific Interaction Is Important For Sequestrationmentioning
confidence: 99%